The impact of wind power on system operation of Singapore power system - Kyaw, May Mee Phyo (2019)
Singapore is the country that is highly relies on the imported oil and gas. In order to step into a more sustainable energy system, Singapore is investing in research on alternative technologies of generating electricity using renewable resources to establish better energy solutions. Among many approaches for sustainable energy solution, this project focuses sole on wind energy. The project is carried out by collecting the daily wind speed across different regions of Singapore based on the Singapore’s wind speed distribution data recorded at meteorological stations. In this project, the wind data are collected for the period of 10 years. The yearly average mean wind speed and maximum wind speed of each weather station is also computed based on the data collected. The individual wind speed data from each weather station is then consolidated into respective regional wind speed. Finally, the average mean wind speed of the whole nation is computed. Based on the data computed, it can be concluded the best region to install a wind turbine to achieve maximum output efficiency from wind energy. Using the wind speed data, a simple Graphical User Interface (GUI) prototype has been implemented using the LabView software. In order to give the detailed insights, three wind turbine models are selected which are the most suitable models for Singapore’s climate and geographical location. The maximum power output obtained from each wind turbine is also calculated. Moreover, the studies on the cost of installation of wind turbines as well as the operation and maintenance cost are also made for analysis purpose. By comparing the power that can be supplied by the wind turbines and power demand, a judgement is made whether it is economical and effective to invest on wind energy in Singapore.